Socio-demographic and environmental determinants of hepatitis: A preventive behaviors in densely populated urban communities - Jannah, Fadillah Rodhatul; Ernawati, Kholis; Wulansari, Rifda; Hidayat, Roni (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: Urban hepatitis A outbreaks in Indonesia highlight the need to understand preventive behaviors beyond biomedical factors. This study applies Green's health behavior theory to examine demographic, behavioral, and environmental determinants of hepatitis A preventive in an urban Jakarta community. The purpose of this study is to identify and analyze the relationship between individual characteristics and preventive behaviors toward Hepatitis A, in order to provide evidence-based recommendations for effective public health interventions. Methods: This study conducted a cross-sectional analytic study among residents aged 15–45 years using a validated questionnaire. Variables included knowledge, attitudes, and information exposure alongside demographics. Data were analyzed with chi-square tests for categorical associations. Findings: Older age, female gender, higher education, employment, better knowledge, positive attitudes, and information exposure were associated with practicing hepatitis A preventive behaviors (e.g., safe water/food handling, hand hygiene) (p < 0.05). The survey in the Kemayoran District showed a high level of compliance in hand washing and clean water use, but inconsistent practices still occurred in relation to thorough cooking of food and technical understanding of the virus etiology. The results of the study identified a significant gap between knowledge and behavior, where moderate attitudes and incomplete health literacy hindered the transition from general awareness to consistent protective actions. Conclusion: Predisposing (knowledge, attitudes), enabling (access to clean water/sanitation), and reinforcing factors (community and health-worker support) jointly predict preventive practices. Findings inform culturally responsive, nurse-led community interventions in low-resource urban settings. Novelty/Originality of this article: This article addresses the gap that most studies in Indonesia have focused only on biomedical or knowledge-based aspects. The study provides a culturally relevant framework for targeted public health interventions in urban communities by integrating demographic, behavioral, and environmental factors.